Financial Institutions And SME Growth In South India through Access, Innovation, And Policy Support - Vijayalakshmi, T.; Kunel , Kishore; Madeshwaren , Vairavel; Manju , K.V. (International Journal of Accounting and Economics Studies, 2025)
India has emerged as one of the fastest-growing economies globally, with Small and Medium Enterprises (SMEs) playing a critical role in this expansion. This study investigates the role of financial institutions in supporting entrepreneurship and business growth among SMEs in South India. It specifically examines the challenges faced by entrepreneurs in accessing finance and evaluates the effectiveness of financial institutions in mitigating these challenges. A sample of 247 SMEs from four South Indian states was selected to analyze the level of institutional support and the impact of financial interventions on business development. The findings reveal that limited access to timely and adequate credit remains a significant barrier to SME growth. However, the study also highlights the proactive role of financial institutions in offering tailored credit schemes, technical assistance, and capacity-building programs. Furthermore, government policies, public-private collaborations, and innovative financial products have been identified as key enablers of a supportive entrepreneurial ecosystem. The study underscores the importance of financial literacy programs and awareness initiatives in empowering entrepreneurs to make informed financial decisions. Overall, this research provides actionable insights for policymakers and financial institutions to strengthen SME development and promote inclusive economic growth in South India.
Keywords: Economy, Growth, Government, Financial Institutions, Support, SMEs